Limits of the Regulatory State Idea: Science and the Cultural Constitution of Capitalist States - Carroll, Patrick (International Journal of Humanities and Social Science Research, 2021)
This paper is an empirically grounded theoretical critique of the idea of the “regulatory state.” The language of the “regulatory state” obscures the nature of the modern state as a constitutive “thing.” The modern state is crucially constituted through the co-productions of science and government. It needs to be investigated in terms of its discursive, practiced, and material dimensions, its meanings, its agencies, and its formation as a material entity composed of land, people and built environment. This critique is needed because the idea of the regulatory state too often leaves implicit the notion that capitalism exists prior to the state, and is thus only “regulated” as such post-hoc. The methods used are those of historical sociological case based analytics, utilizing archival materials. The purpose is to challenge the taken-for-granted distinction between the state and capitalist social organization. The implications for further research are the need to delve deeper into the complex entanglements of state and society, and the ironic role that science as culture played in constructing both those concrete entanglements and the abstract bounded categories that obscure them.